Design and manufacture of a system for measuring the thermal conductivity of conductive materials (Copper, Aluminum, Brass Alloy) - Siham Younis Mustapha (مجلة التربية والعلم, 2013)
In this research we designed and constructed a system from a local materials and tested for measuring the thermal conductivity coefficient of thermally good conducting materials  in the temperature range (25–150 c°). We measure the thermal conductivity of  three conducting materials (Copper, Aluminum and Brass alloy), The thermal conductivity  measuring result show a good convergence with standard values (Cu 416W/m.c° with a percentage error 3.7%), (Al 244 W/m.c° with a percentage error 2.9 %), (Brass alloy 112,5 W/m.c° with a percentage error 2.2 %). The thermal conductivity of copper and aluminum show decreases of conductivity with increasing temperature.